1984: THE MASTERPIECE THAT KILLED GEORGE ORWELL (CHAPTER I) - Kudratova, Sitora (Eurasian Journal of Academic Research, 2023)
The novel 1984, the final masterpiece of George Orwell, was published in 1949 which is a dystopian social science fiction novel. Thematically, the core idea of his masterpiece is about the consequences of totalitarianism, mass surveillance and repressive regimentation of people and behaviours within society. Orwell inspired writing his last novel on dystopian novel “We”, the production of Russian writer Yevgeny Zamyatin, which was introduced him by literature professor Gleb Struve in 1944. However, later in 1946, George Orwell wrote about dystopian novel “Brave New World” by Aldous Huxley in his article "Freedom and Happiness" for the Tribune. In his article he mentioned about similarities to “We”. By this time the political satire “Animal Farm” which Orwell published in 1945, had scored a critical and commercial hit and also raised his profile. So then, Orwell decided to write his novel “1984”.